Polymérisation des énantiomères d'un acide α-aminé : Stéréosélection et amplification de l'asymétrie - G. Spach (CHIMIA)
Proteins of higher living systems are built only with amino acids the configuration of which is L. However the synthesis of these building blocks in abiotic conditions leads to the formation of a racemic mixture.